Analisis Tindak Tutur Ekspresif Novel Prasetyane Wanita Karya Tulus Setiyadi sebagai Bahan Ajar Bahasa Jawa di SMA - Nurlaila Rizqillah Sofyani; Raheni Suhita; Kenfitria Wijayanti (Universitas Sebelas Maret, 2022)
The research aimed to describe and explain the forms of speech acts expressive novel Prasetyane Wanita by Tulus Setiyadi, and the relevance of the novel Prasetyane Wanita by Tulus Setiyadi with javanese language teaching materials in senior high school. The method in this research is a qualitative with a content analysis approach using pragmatic theory to determine the form of expressive speech acts contained in novel Prasetyane Wanita by Tulus Setiyadi. The data source in this research is a novel entitled Prasetyane Wanita by Tulus Setiyadi which was published by Pustaka Ilalang in August 2020. The data collection techniques used were documentation or document analysis techniques, and interviewing informants. The validity of data using theoretical triangulation and source triangulation. The data analysis technique used is interactive analysis technique. The results of this study indicate that the forms of expressive speech acts found in novel Prasetyane Wanita by Tulus Setiyadi include expressive speech acts of include 4 expressive speech acts of thanking, 5 expressive speech acts of praising,3 expressive speech acts of pardoning,4 expressive speech acts condoling, 1 expressive speech acts of congratulating, and 5 expressive speech acts of blaming. In addition, novel Prasetyane Wanita by Tulus Setiyadi is relevant if it is used as teaching material for Javanese language in high school, precisely at KD 3.2, namely